1977
DOI: 10.1073/pnas.74.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Comparative subunit structure of HeLa, yeast, and chicken erythrocyte chromatin.

Abstract: We have compared the chromatin subunit structure of yeast, HeLa, and chicken erythrocyte by analyzing the DNA fragments produced by in situ digestion with staphylococcal nuclease (EC 3.1.4.7) and DNase I (EC 3.1.4.5). The repeat size of the chromatin varies among (and within two of) the three organisms but the size and the structure of the most nuclease-resistant "core" of the repeat is the same. Thus, the interspecies differences in repeat size are due to different lengths of nuclease-sensitive "spacer" DNA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
74
1

Year Published

1977
1977
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(87 citation statements)
references
References 22 publications
12
74
1
Order By: Relevance
“…2c). This DNA may, however, have been produced by unfolding from the nucleosome (or core particle), a proposal that explains the same phenomenon observed in electron microscope spreads of yeast chromatin (29), which, like neuronal chromatin, also has a very short repeat length (21,22). This latter interpretation is also consistent with the reduced dichroism measurements of depleted neuronal chromatin, which indicated a substantially unwound fiber, even in the presence of divalent cations (Table I).…”
Section: Electron Microscopysupporting
confidence: 79%
See 1 more Smart Citation
“…2c). This DNA may, however, have been produced by unfolding from the nucleosome (or core particle), a proposal that explains the same phenomenon observed in electron microscope spreads of yeast chromatin (29), which, like neuronal chromatin, also has a very short repeat length (21,22). This latter interpretation is also consistent with the reduced dichroism measurements of depleted neuronal chromatin, which indicated a substantially unwound fiber, even in the presence of divalent cations (Table I).…”
Section: Electron Microscopysupporting
confidence: 79%
“…However, there is no experimental precedent for H 1 induced higher order folding in a chromatin with a repeat length < 168 base pairs . In yeast chromatin, the absence of an H1 has led to the suggestion that the 30-nm fiber observed (29) with this very short repeat length chromatin (<168 base pairs, (21,22)) may be stabilized by an as yet unidentified molecule (29).…”
Section: Discussionmentioning
confidence: 99%
“…The size of the repeating unit ranges from 154 base pairs in Aspergillus nidulans [2] to 241 base pairs in the chromatin of sea urchin sperm [7]. As yet the origin of this phenomenon has not been explained but a few possible causes of the observed variability have been excluded [7][8][9]; indeed it has been shown that the rate of cell division, the stage in the cell cycle, the genomic activity, the phosphorylation of H1 and the acetylation of histone Ha and H4 could not be correlated to the variation of the repeat length of chromatin. Noll [1 ] and Morris [2] have suggested that there may be a relationship between the structure of historic H1 (as expressed by the content of basic amino acids) and the length of the DNA repeat in chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…The variability of the DNA repeat length in chromatin of eukaryotes is now well documented [1][2][3][4][5][6][7][8][9][10][11]. The size of the repeating unit ranges from 154 base pairs in Aspergillus nidulans [2] to 241 base pairs in the chromatin of sea urchin sperm [7].…”
Section: Introductionmentioning
confidence: 99%
“…In order to confirm that the primary structure differences apply to the entire molecule we have elucidated the completc structure of yeast histone H3. In view of the evidence accumulating which indicates that the packing of DNA in the yeast cell nucleus is closely related to that found in higher organisms [3,4], the existence of major structural changes in the conservative histones could throw a new light on their origin and structurefunction relationships.The genome of yeast is about a hundred times smaller than that of higher vertebrates. This results in a very low histone concentration in the total cell protein.…”
mentioning
confidence: 99%